PERAN SUBAK DALAM MENJAGA KEBERLANJUTAN COMMUNITY BASED ECOTOURISM - Ni Kadek Winda Yanti (STABN Raden Wijaya Wonogiri, 2023)
This research aims to comprehend Subak Sembung's means to maintain the sustainability of Community Based Ecotourism in Subak Sembung, Peguyangan. Since, Subak plays an important role in preserving the environment and culture in its area which are fundamental elements needed to implement ecotourism in Subak Sembung. The research uses qualitative data with qualitative descriptive methods. Data collection methods were conducted using observation techniques, in-depth interviews and documentation. The purposive sampling technique was used to determine the informant in this research. It found that there are two important aspects in maintaining the sustainability of ecotourism in this area, namely the role of Subak member communities and the role of Subak organization in controlling and distributing rights and obligations to its members. This research provides an illustration of how traditional bodies such as Subak play an important role in preserving the environment and the socio-cultural values inherent in it. Keywords : Subak, Ecotourism, Communities, Sustainability